2015
DOI: 10.1515/eurodl-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

A Learning Analytics Methodology for Detecting Sentiment in Student Fora: A Case Study in Distance Education

Abstract: Online fora have become not only one of the most popular communication tools in e-learning environments, but also one of the key factors of the learning process, especially in distance learning, as they can provide to the students involved, motivation for collaboration in order to achieve a common goal. The purpose of this study is to analyse data related to the participation of postgraduate students in the online forum of their course at the Hellenic Open University. The content of the messages posted is anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The authors themselves recognized this limitation, claiming that real-time analysis, which DIANA 2.0 does, would have enriched the results. Kagklis, Karatrantou, Tantoula, and Panagiotakopoulos (2015) had similar results, and the reason is the same lack of real-time analysis as in the previous case. To support this argument, we found a correlation of 68% between grades and level of participation.…”
Section: Discussionsupporting
confidence: 63%
“…The authors themselves recognized this limitation, claiming that real-time analysis, which DIANA 2.0 does, would have enriched the results. Kagklis, Karatrantou, Tantoula, and Panagiotakopoulos (2015) had similar results, and the reason is the same lack of real-time analysis as in the previous case. To support this argument, we found a correlation of 68% between grades and level of participation.…”
Section: Discussionsupporting
confidence: 63%
“…Ma et al ( 2015 ) used learning analytics to track data related to teaching and learning activities to build an interaction-activity model to demonstrate how the instructor’s role has an impact on students’ engagement activities. An analysis of student emotions through their participation in forums and their performance in online courses can serve as the basis to model student engagement (Kagklis et al 2015 ). They further observed that the students’ participation in forums was not directly associated with their performances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ma et al (2015) used learning analytics to track data related to teaching and learning activities to build an interaction-activity model to demonstrate how the instructor's role has an impact on students' engagement activities. An analysis of student emotions through their participation in forums and their performance in online courses can serve as the basis to model student engagement (Kagklis et al 2015). They further observed that the students' participation in forums was not directly associated with their performances.…”
Section: Learner Engagement In Online Coursesmentioning
confidence: 99%